2002
DOI: 10.1039/b207945c
|View full text |Cite
|
Sign up to set email alerts
|

The origin of electrochemical activity in Li2MnO3

Abstract: The electrochemical activity of Li2MnO3 in non-aqueous media has been investigated and found to involve neither Mn(4+)-Mn5+ oxidation nor simultaneous O2- removal but exchange of Li+ by H+, the latter being generated in the electrolyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
174
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(178 citation statements)
references
References 18 publications
4
174
0
Order By: Relevance
“…These materials contain Ni in the formal oxidation state of +3 rather than +2 as in the previous reports of anomalously high capacity materials. The discharge capacities obtained, as high as 240 mAh g −1 , were much greater than expected for 1:1 solid solutions of Li 2 MnO 3 -LiNi 1−x Co x O 2 .H o w e v e r ,e v e nf o r Li 2 MnO 3 it has been shown that charging to voltages greater than 4.3-4.4 V induces an unexpected reversible capacity [6].…”
Section: Introductionmentioning
confidence: 94%
“…These materials contain Ni in the formal oxidation state of +3 rather than +2 as in the previous reports of anomalously high capacity materials. The discharge capacities obtained, as high as 240 mAh g −1 , were much greater than expected for 1:1 solid solutions of Li 2 MnO 3 -LiNi 1−x Co x O 2 .H o w e v e r ,e v e nf o r Li 2 MnO 3 it has been shown that charging to voltages greater than 4.3-4.4 V induces an unexpected reversible capacity [6].…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, several publications have appeared with different procedures for activation of Li 2 MnO 3 and with varying capacity values. [5][6][7][8][9][10][11][12][13][14] The initial discharge capacity values are generally high for the activated phases of Li 2 MnO 3 , but cycling instability is observed in all reports. In order to enhance the cycling stability, composites of Li 2 MnO 3 with other layered lithiated transition metal oxides such as LiCoO 2 are studied.…”
mentioning
confidence: 99%
“…9). The unmarked voltage plateau is a characteristic of discharge process of Li 2 MnO 3 materials (Robertson and Bruce, 2002;Yue et al, 2008;Huang et al, 2009). Note that extending the voltage cutoff to 2.0 V resulted in higher capacity (157.5, 168.3 and 121.2 mAh g −1 for samples annealed at 550, 650 and 750°C); however, the capacities decayed more quickly.…”
Section: Resultsmentioning
confidence: 94%